Trade deflection with transaction costs: The case of restricted origin principle - Andreas Haufler (Universität Konstanz, Sonderforschungsbereich 178 - Internationalisierung der Wirtschaft, 1994)
The paper analyzes the implications of allowing for trade deflection under the restricted origin principle. It is shown that (a) producer trade deflection leads to circular trade and must be ruled out to obtain a trade equilibrium, (b) consumer trade deflection will not occur in a Nash equilibrium when transaction costs are linear (zero) and tax rates are endogenized, (c) with strictly convex transaction costs model results do not differ qualitatively from those obtained in the absence of trade deflection. Together, these results give some theoretical support for the no cross-hauling assumption typically used in multi-country trade modelling.
Keywords: F15; H73; 330; tax differentials; cross-hauling; Ursprungslandprinzip; Verbrauchsteuer; EU-Binnenmarkt; Transaktionskosten; Interregionaler Handel; Theorie